Implementation Of Multiliteration Pedagogy In Education: A Socio-Cultural Perspective - Akhtar, Jamil Akhtar; Gaffar, Abdul; Arifin, Samsul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
Implementing social and cultural multiliteracies in education presents both challenges and opportunities. Embracing diverse forms of literacy can enhance educational strategies, fostering social and critical thinking skills that benefit students and society. It is imperative for educational institutions to actively adopt multiliteracy approaches that reflect the diversity of our society. This preparation is essential for students to succeed in an interconnected world. Integrating social and cultural multiliteracies into teaching practices is crucial for creating inclusive and dynamic learning environments that cater to diverse student backgrounds. Such an approach promotes a sense of belonging and appreciation for different cultures, enriching the educational experience for all individuals involved. Educators can develop proactive strategies by acknowledging and addressing the challenges of implementing social and cultural multiliteracies. This may include providing professional development opportunities, incorporating culturally relevant materials into the curriculum, and engaging the community to gain deeper cultural insights. Ultimately, embracing social and cultural multiliteracies in education leads to more effective and inclusive educational practices that prepare students for success in a diverse world